Characterization of a Granulovirus Isolated from Epinotia aporema Wals. (Lepidoptera: Tortricidae) Larvae - Sciocco de Cap, Alicia (2001)
A granulovirus (GV) isolated from Epinotia aporema (Lepidoptera: Tortricidae) - a major soybean pest - was studied in terms of its main morphological, biochemical, and biological properties. The ovoidal occlusion bodies were 466 by 296 nm in size, and their most prominent protein had an apparent molecular mass of 29 kDa. Its amino-terminal sequence was remarkably homologous to that of the granulins of other GVs. The DNA genome size was estimated to be 120 kbp. The high specificity and pathogenicity of this newly described granulovirus (EpapGV) indicate that it is indeed a good candidate for the biological control of this pest.